Strengthening of Digital Media Literacy-Based Character Education on Hoax News Spreading to Students (Case Study on Citizenship Education Learning in SMP Negeri 2 Bandung) - Vita Sevia Nanda; Dasim Budimansyah (AIBPM Publisher, 2020)
Through citizenship education subjects’ students can grow and develop digital media literacy. This digital media literacy includes improving knowledge and skills, and awareness will be the use of digital media and the Internet. The method used in this research is a case study with a qualitative approach, which will be applied in schools. The results of this study show: how the implementation and success of character education based on digital media literacy based on the spread of hoax news to students in citizenship education learning. After conducting research, the program of strengthening character education through digital literacy-based citizenship education subjects is successful in counteracting the spread of hoax news, and can foster student awareness in the use of digital media and the internet.